EFEKTIVITAS KINERJA TENAGA KERJA KONTRAK DAERAH DI DINAS KEHUTANAN KABUPATEN KUTAI BARAT - Budi Prasetiya (Jurnal Administrative Reform, 2017)
This article aim is to describe and analyze the effectiveness of the work performance of labor contract at the same time identify the factors supporting and inhibiting the effectiveness of the labor contract, the type of research conducted included in the descriptive qualitative research. The conclusions based on the data are using analysis data and interactive models. According to the results of research it found that the performance of the work labor contract at the Forest Departemen Kabupaten Kutai Barat can be quite good. It can be known from the ability of employees the perform their duties, both in terms of aspects of work quality and quantity of work and time of completion of work.Keyword : Effectiveness, Performance, Labor Contract, Forestry Service